Foreign Direct Investment in Tourism and the Feasibility of Incorporating the United Nation Guiding Principles on Business and Human Rights in Indonesia - I Gusti Ngurah Parikesit Widiatedja (Yuridika, 2022)
Foreign direct investment (FDI) is critical to Indonesia's economic development. Tourism is one of the most appealing investment industries. It has made a significant contribution to employment creation, tax revenue and domestic value addition. However, FDI in tourism has had negative environmental consequences. Moreover, Indonesian trade agreements and investment treaties do not reflect environmental concerns. The schedule under the General Agreement on Trade in Services (GATS) follows a similar trend, although other countries’ practices have shown that Indonesia can add this concern. Domestic laws and policies are also silent because the goal of economic growth outweighs protecting the environment. The United Nations Guiding Principles on Business and Human Rights (Guiding Principles) govern states' obligations to defend human rights and companies' obligations to respect and give remedy. This article examines the feasibility of incorporating the Guiding Principles into FDI in tourism. The Guiding Principles, together with the Global Code Ethics for Tourism, would provide a starting point for more robust legal frameworks for foreign tourism companies and emphasise sustainable development.